Respiration Monitoring of All Occupants in a Vehicle Using Time-Division Multiplexing FMCW Radar Based on Metasurface Technology - Kang, Wei; Zhou, Chenwei; Wu, Wen (IEEE transactions on microwave theory and techniques, 2024)
Noninvasive respiration monitoring of the driver and all passengers in a vehicle simultaneously with microwave radar technology is crucial for assessing their physiological status. To achieve this, the radar system must be able to monitor and distinguish the respiration signals of multiple closely seated targets in the presence of strong clutter interference within the vehicle. To overcome these challenges, a time-division multiplexing (TDM) frequency modulation continuous-wave (FMCW) radar in conjunction with a multibeam metasurface lens antenna and multifunctional metasurface tags is proposed to estimate the respiration rates of multiple targets in a vehicle. On the one hand, the metasurface lens antenna is employed to steer four sequential-scanning beams toward different human subjects in the vehicle and distinguish them from other closely seated targets. Compared to the conventional phased array, this metasurface antenna eliminates the need for 2-D T/R components. On the other hand, the designed passive metasurface tags are attached to the seat belts worn by human subjects, which can capture the phase changes caused by the movements of the human chests to estimate their respiration rates. In particular, the tags exhibit both retroreflection and polarization selection characteristics, which can retroreflect incident linearly polarized waves at a given angle, thereby improving the signal-to-clutter ratio (SCR) of the respiration signal to combat the strong clutter and multipath reflection in the vehicle. Experimental results demonstrate that the proposed radar can estimate the respiratory rates of all occupants in an in-vehicle scenario, proving the effectiveness of the proposed radar scheme.